Professor Ts. Dr. Mohd Rashid develops leadership assessment instrument using core value indicators - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 8 November 2023 – A Professor at the Centre for Mathematical Sciences (PSM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Ts. Dr. Mohd Rashid Ab Hamid, 43, has created a leadership assessment instrument using core value indicators.